Motives of Freud’s Essay "Das Unheimliche" in the Collection of Stories "Žena koja zaustavlja satove" by Kornelije Kvas - Lazić Gavrilović, Aleksandra M. (Collection of Papers of the Faculty of Philosophy in Priština, 2025)
The article analyzes striking similarities between the motifs in 2023 short story collection The Woman Who Stops the Clocks (Žena koja zaustavlja satove) by Kornelije Kvas and Freud’s 1919 essay The Uncanny (Das Unheimliche). Following Zeno’s Path (Zenonov put), The Woman Who Stops the Clocks (2023) is the second work of fiction by Kornelijе Kvas. The book consists of a prologue and nine seemingly unrelated stories of diverse themes, each with unexpected, fateful twists that open the door to various interpretations. The complexity of the structure and the polysemy of the text are revealed gradually; it often requires revisiting previously read material to notice that the same obscure characters and unusual motifs reappear cyclically throughout the stories. In contrast to the author’s debut, which is characterized by postmodern literary techniques, The Woman Who Stops the Clocks features thematic and motif complexes and literary techniques that align more with the modernist poetics. Despite all the significant correspondences, the fact that Kvas did not include The Uncanny in his “list of literature” suggests that the motifs in his book are not directly inspired by Freud’s essay. Demystifying the hidden meanings of Kvas’s motifs through Freud’s essay The Uncanny opens up one interpretative possibility that reveals a new, initially hidden meaning of the book, concealed in the unconscious. This primarily concerns the Oedipus complex, which is central to psychoanalytic theory and Freud’s theory of art. However, when Freudian psychoanalysis and the essay The Uncanny are incorporated into the interpretation, the hidden (repressed) meaning of Kvas’s book becomes apparent, revealing it not merely as a collection of short stories but as a multi-layered, cohesive work with a novel-like structure.